LISTERIA MONOCYTOGENES INFECTION IN FREE-RANGING RED FOXES (VULPES VULPES) AND EURASIAN LYNX (LYNX LYNX) IN SWITZERLAND. - Heiderich, Elisabeth; Origgi, Francesco C; Pisano, Simone R R; Kittl, Sonja; Oevermann, Anna; Ryser-Degiorgis, Marie-Pierre; Marti, Iris A (Journal of Zoo and Wildlife Medicine, 2024)
Listeria monocytogenes is an ubiquitous environmental saprophytic bacterium causing listeriosis in domestic animals, humans, and occasionally wildlife. In animals, this foodborne zoonotic disease mainly occurs in ruminants and it is rare in carnivores. Seven red foxes (Vulpes vulpes) and one Eurasian lynx (Lynx lynx) were diagnosed with listeriosis between 2010 and 2021 at the Institute for Fish and Wildlife Health, Bern, Switzerland. Necropsy and histopathology revealed meningitis (six of seven red foxes), hepatitis (six of seven red foxes), pneumonia (five of seven red foxes), splenitis (two of seven red foxes) and splenomegaly (the Eurasian lynx, two of seven red foxes). Listeria monocytogenes was isolated from either lung, spleen, liver, or kidney of all animals. Serotyping detected L. monocytogenes serotype 1/2a in five red foxes and the Eurasian lynx and serotype 4b in two red foxes. Six red foxes were positive for canine distemper virus (CDV) by polymerase chain reaction, whereas the Eurasian lynx and one red fox were negative. One red fox that was positive for CDV and listeriosis was also diagnosed with salmonellosis. The identified L. monocytogenes serotypes are among the three most frequently isolated serotypes (1/2a, 1/2b, and 4b) from food or the food production environment and those that cause most listeriosis cases in humans and animals. Coinfection with CDV in six red foxes questions the role of CDV as potential predisposing factor for septicemic listeriosis. The detection of listeriosis in the regionally endangered Eurasian lynx and in carnivores highly abundant in urban settings, such as red foxes, reinforces the importance of wildlife health surveillance in a One Health context and adds the Eurasian lynx to the list of carnivores susceptible to the disease. Further investigations are required to assess the prevalence and epidemiology of L. monocytogenes in free-ranging carnivores and its interaction with CDV.